Exploring mechanisms for spring bloom evolution: contrasting 2008 and 2012 blooms in the southwest Pacific Ocean. (9th January 2018) - Chiswell, Stephen M; Safi, Karl A; Sander, Sylvia G; Strzepek, Robert; Ellwood, Michael J; Milne, Angela; Boyd, Philip W
Abstract: Observations from two research cruises made in 2008 and 2012 to east of New Zealand are put into context with satellite data to contrast and compare surface chlorophyll a evolution in the two years in order to explore mechanisms of phytoplankton bloom development in the southwest Pacific Ocean. In 2008, surface chlorophyll a largely followed the long-term climatological cycle, and 2008 can be considered a canonical year, where the autumn bloom is triggered by increasing vertical mixing at the end of summer and the spring bloom is triggered by decreasing vertical mixing at the end of winter. In contrast, 2012 was anomalous in that there was no autumn bloom, and in early spring there were several periods of sustained increase in surface chlorophyll a that did not become fully developed spring blooms. (In this region, we consider spring blooms to occur when surface chlorophyll a exceeds 0.5 mg m -3 ). These events can be related to alternating episodes of increased or decreased vertical mixing. The eventual spring bloom in October was driven by increased ocean cooling and wind stress (i.e. increased mixing) and paradoxically was driven by mechanisms considered more appropriate for autumn rather than spring blooms.